Metal ions-induced structural modification of extracellular polymers: Impact of the valence on sludge biodegradability and dewaterability. (October 2022) - He, Junguo; Zou, Xiang; Zhang, Pengfei; Zhong, Yijie; Pan, Xinlei; Zhang, Jie; Wu, Xuewei; Li, Biqing; Tang, Xia; Xiao, Xiannian
Abstract: Through the addition of metal ions, this study developed an innovative strategy for altering the structure of EPS and the chemical properties of waste activated sludge, which would consequently affect sludge dewaterability and biodegradability. The valence of the metal cations is an important index to predict its effect on EPS. With multivalent cations, the particle size and zeta potential of EPS increased by about 8%–11% and 25%–50%, respectively, however, the extractable tightly-bound EPS (TB-EPS) was reduced by about 15%–20%. On the other hand, VSS increased by 9.82% with external monovalent cations. In contrast with multivalent cations, monovalent cations would lower the density of EPS, destroy its structure, and allow the trapped compounds to escape. Therefore, monovalent metal ions are excellent additives to improve the dewaterability and biodegradability of sludge. These findings not only provide clues for predicting the interaction between EPS and uncommon cations but also offer a new idea to premeditatedly modify the EPS structure, providing a metal ion regulation-based way for improving sludge dewaterability or enhancing anaerobic fermentation performance. Highlights: Valence is an important index to estimate the interaction between cations and EPS. Protein-like substances are the main components that interact with cations in EPS. Electrostatic force and bridge effect help multivalent cations to stabilize EPS. Monovalent cations replace multivalent ones in EPS and weaken the binding force. Monovalent cations aid biodegradation and dewatering opposite to multivalent ones.